(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Through athletics, volleyball players can improve their physical fitness as well as their sense of teamwork and sportsmanship. It’s interesting to note that once the K–12 curriculum was established in the Filipino educational system, there wasn’t much information in the literature about how senior high school students perform academically. Many researchers have investigated the challenges encountered by varsity athletes that affect their academic performance, and all of them have concluded that time management skills may be necessary to keep up with the assignments from teachers and coaches. In addition, they must strike a balance between their academic and athletic performance. The ability to prioritize tasks and make a "to-do list" is a skill that is increasingly important for varsity athletes nowadays if they are to complete their daily tasks and academic assignments on time and avoid any difficulties.